Lack of intestinal epithelial atg7 affects paneth cell granule formation but does not compromise immune homeostasis in the gut. - Günther, Claudia; Martini, Eva; Waldner, Maximilian; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph; et al. (Clinical & Developmental Immunology, 2012)
Genetic polymorphisms of autophagy-related genes have been associated with an increased risk to develop inflammatory bowel disease (IBD). Autophagy is an elementary process participating in several cellular events such as cellular clearance and nonapoptotic programmed cell death. Furthermore, autophagy may be involved in intestinal immune homeostasis due to its participation in the digestion of intracellular pathogens and in antigen presentation. In the present study, the role of autophagy in the intestinal epithelial layer was investigated. The intestinal epithelium is essential to maintain gut homeostasis, and defects within this barrier have been associated with the pathogenesis of IBD. Therefore, mice with intestinal epithelial deletion of Atg7 were generated and investigated in different mouse models. Knockout mice showed reduced size of granules and decreased levels of lysozyme in Paneth cells. However, this was dispensable for gut immune homeostasis and had no effect on susceptibility in mouse models of experimentally induced colitis.